OP0043 WITHDRAWAL OF A LOW DOSE (5 MG) OF CORTICOSTEROIDS IN SYSTEMIC LUPUS IN REMISSION FOR MORE THAN A YEAR IS AT RISK OF RELAPSE – THE CORTICOLUP TRIAL. (June 2019) - Pha, Micheline; Mathian, Alexis; Haroche, Julien; Hié, Miguel; Cohen, Fleur; Huong, Du Boutin-Le Thi; Chambrun, Marc Pineton de; Cherin, Patrick; Devilliers, Hervé; Amoura, Zahir
Abstract : Background: Glucocorticoids (GCs) are a mainstay of treatment for patients with SLE but are associated with significant adverse effects. Some SLE patients are maintained for a long-term under a low dose of prednisone to prevent relapse. There is no scientific data to sustain this therapeutic strategy. Objectives: We hypothesized that maintaining a daily dose of 5 mg prednisone in patients with an inactive SLE for at least a year would prevent the risk of relapse. Methods: The CORTICOLUP study (NCT02558517 ) was a prospective randomized, open-labeled, controlled, monocentric study sought to compare maintenance vs withdrawing of low-dose of prednisone (5mg) to reduce SLE flares, conducted from January 2014 to March 2017. Inclusion criteria were SLE patients who during the year preceding the inclusion had 1/an inactive SLE defined by a SLEDAI-2K score ≤ 4, a BILAG-2004 index C, D or E in all systems and a PGA =0 and 2/a stable SLE treatment including prednisone 5 mg daily. The primary end point was the number of patients with flares during 12 months of follow-up defined by the revised-SELENA SLEDAI Flare Index (rSFI). Secondary outcomes were occurrence of a BILAG scores A or B ≥1, clinical SLEDAI-2k >0, PGA ≥0.5 and increase of the SLICC damage index (SDI). All patients were included in the intention-to-treat analysis. Results: A total of 124 patients (61 in the maintenance group and 63 in the withdrawal group) were included. No patients were lost to follow up. At baseline There were no significant differences between the maintenance and the withdrawal group with respect to: duration of SLE [mean (±standard deviation) duration of 11.8 (±0.9) versus 13.1 (±1.0) years], duration of remission [55.7 (±5.8) vs 67.5 (±6.8) months], HCQ treatment [98.2% vs 100.0%], immunosuppressive drugs [27.9% vs 25.4%], previous renal involvement [34.4% vs 41.3%], low C3 [16.4% vs 15.9%], positive Farr test [47.5% vs 46.0%], and SDI [mean index of 0.5 (±0.1) vs 0.7 (±0.2)]. There were significantly more flares in the withdrawal group compared to the maintenance group (17 flares versus 4, p=0.0034 using the Fisher's exact test). Mild or moderate flares were more frequent in the withdrawal group compared to the maintenance group (12 vs 3, p=0.029). The occurrence of severe flare was not significantly different between the two groups (5 vs 1, p = 0.208). More than two-thirds of the flares in the withdrawal group occurred within the first six months. Within the withdrawal group, using forest plot analysis, no significant association was found between the occurrence of a flare and age, sex, duration of SLE, duration of SLE remission, duration of GCs treatment, immunosuppressants and serological SLE activity at randomization. Four patients in the withdrawal group and none in the maintenance group experienced damage: 2 osteoporosis bone fractures, 1 hydroxychloroquine retinopathy and 1 cataract. Conclusion: Withdrawal of low dose of steroids in patients with inactive SLE and stable therapeutic regimen for more than a year is associated with a high risk of relapse. Disclosure of Interests: None declared